Effects of chronic Staphylococcus aureus infection on immunological parameters and functionality of macrophages isolated from bovine mammary secretions - Renna, María Sol; Silvestrini, Paula; Beccaria, Camila; Velázquez, Natalia S.; Baravalle, Celina; Engler, Carolina; Pereyra, Elizabet Amanda Lorena; Calvinho, Luis Fernando; Dallard, Bibiana Elisabet (Elsevier, 2019)
The aim of this study was to characterize the effects of chronic S. aureus intramammary infection (IMI) on local innate and adaptive immune response during active involution. Cows in late lactation that were either uninfected or with chronic naturally acquired S. aureus IMI were included in this study. The levels of interleukin (IL)-1β, IL-6 and IL-4 were significantly higher in mammary secretions of S. aureus-infected quarters compared with uninfected at d 7, 14 and 21 of involution. Lactoferrin (Lf), total IgG and S. aureus specific IgG1 levels were significantly lower in mammary secretions of infected quarters compared with uninfected during the first three weeks of involution. The amount of intracellular reactive oxygen species (ROS) produced per macrophage, was significantly higher in mammary secretions of infected quarters compared with uninfected at d 14 post drying off. Nitrite production was significantly higher in phagocytes from infected mammary secretions compared with uninfected at d 7 and 14 post drying off. Chronic S. aureus IMI altered normal secretion composition during bovine mammary gland involution. The high IL-1β and IL-6 levels and increased functionality of macrophages in mammary secretions of infected quarters could be a result of the chronic inflammatory environment triggered by the presence of viable bacteria in mammary tissue. The lower levels of total and S. aureus specific antibodies and other immune factors in mammary secretion during this period may reduce the natural defense potential of the gland contributing to S. aureus persistence.